Impact of roasting conditions on physicochemical, taste, volatile, and odor-active compound profiles of Coffea arabica L. (cv. Yellow Bourbon) using electronic sensors and GC–MS-O using a multivariate approach - Seong Jun Hong; Chang Guk Boo; Sojeong Yoon; Hyangyeon Jeong; Seong Min Jo; Moon Yeon Youn; Jae Kyeom Kim; Young Jun Kim; Eui-Cheol Shin (Food Chemistry: X, 2024)
This study investigated the effects of roasting conditions on the physicochemical, taste, and volatile and odor-active compound (OAC) profiles of Coffea arabica L. At 150 ℃, roasting increased chlorogenic acid, total flavonoids, and caffeine concentrations. However, umami and sourness sensor decreased during the roasting process. At 210 ℃ roasting, total flavonoid and caffeine concentrations increased during the roasting process. Aldehydes, ketones, and sulfur-containing compounds dramatically increased during the roasting at 210 ℃ for 20 and 30 min in E-nose analysis. Pyrazines were mainly generated during the roasting at 210 ℃ for 20 and 30 min, and pyrazines showed the highest concentrations among all OACs in GC-olfactometry (GC-O) analysis. E-tongue data showed the separation of beans by roasting temperature. However, the E-nose and GC-O data showed the separation of beans by both roasting temperature and time via multivariate analysis. We identified similar results and patterns in the E-nose and GC-O analyses.